2019
DOI: 10.1002/minf.201900112
|View full text |Cite
|
Sign up to set email alerts
|

Omics‐based Identification of Glycan Structures as Biomarkers for a Variety of Diseases

Abstract: Glycans play important roles in cell communication, protein interaction, and immunity, and structural changes in glycans are associated with the regulation of a range of biological pathways involved in disease. However, our understanding of the detailed relationships between specific diseases and glycans is very limited. In this study, we proposed an omics-based method to investigate the correlations between glycans and a wide range of human diseases. We analyzed the gene expression patterns of glycogenes (gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Tumor-associated glycan signatures are products of biosynthetic machineries that are presumably altered in cancer. Changes in glycogene expression are widely observed in cancer ( 16 , 17 ), but a cohesive picture that relates these transcriptomic changes to altered glycosylation of functional relevance is lacking. Furthermore, the mechanisms driving altered glycogene expression have not been addressed.…”
mentioning
confidence: 99%
“…Tumor-associated glycan signatures are products of biosynthetic machineries that are presumably altered in cancer. Changes in glycogene expression are widely observed in cancer ( 16 , 17 ), but a cohesive picture that relates these transcriptomic changes to altered glycosylation of functional relevance is lacking. Furthermore, the mechanisms driving altered glycogene expression have not been addressed.…”
mentioning
confidence: 99%
“…Moreover, the pathways of mannose type O-glycan biosynthesis and other types of O-glycan biosynthesis were decreased in H-Pro group on day 42. Report indicated that changes in O-glycans biosynthesis were found in many diseases, like intestinal bowel disease and malignant melanoma ( Akiyoshi et al, 2020 ). Therefore, decreased the pathway related to O-glycan biosynthesis also implied the beneficial roles of B. subtilis HW2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different N-glycan structures in serum IgGs that have no direct relationships with cancer cells can be useful distinguish healthy individuals from patients with lung, gastric, prostate, ovarian, and breast cancers ( 27 31 ). Moreover, several glycan structural changes have been identified on specific proteins in different types of cancer, such as gastric, nasopharyngeal or endometrial cancer ( 32 ), and immunoglobulins or glycoregulatory proteins are aberrantly expressed in EC ( 33 , 34 ). These published reports clearly indicate the diverse glycan structures, abundantly present in the human blood circulation and tissues, and can potentially serve as promising biomolecules for biomarker discovery ( 35 ).…”
Section: Introductionmentioning
confidence: 99%